Determinants of The Special Groups Participation in Government Procurement Opportunity in Tanzania. - Tesha, A.K.; Nsimbila, P.M. (AFRICAN JOURNAL OF APPLIED RESEARCH, 2022)
Purpose: This study aimed to investigate the key determinants influencing special groups' participation in government procurement opportunities in Tanzania. The benefits that special groups participate in the government procurement opportunity have to offer in terms of enhancing Tanzanian government efficiency in eradicating poverty and reducing the unemployment rate, mean that we should act to surmount existing challenges. Design/ Methodology/ Approach: A study involved a mixed research approach involving both quantitative and qualitative. The Snowball sampling technique was used to select 100 respondents as a sample size, of these, 94 responded to the questionnaire. However, data were collected through questionnaires and an interviews guide. Findings: The result showed that information factors, financial factors and regulatory factors had significant effects on the special groups' involvement in the government procurement opportunity with P-values p=0.029, 0.014, 0.012 respectively, while Technical factors and ethical factors had no significant effects on special group participation in the government procurement opportunity with P-value p=0.055 and p=0.190 respectfully. Perceptions of not winning by the special groups, and inferiority among special groups individually and collectively, however, hinder the involvement in the government procurement market. Research Limitations: on the determinants of special groups' participation in the public procurement opportunity. Minority groups were included as new variables. Practical Implication: The result of this study will be beneficial to the top governance, mutually at nationwide and organization levels in Tanzania, of the advantage that may accumulate from the full participation of the special groups in the Public procurements market. Social Implication: The Tanzania Procurement policy for special groups should promote subcontracting, funding mechanisms and teaming for special groups to participate in the government procurement opportunity. Originality/ Value: Perceptions of not winning by the special groups, and inferiority among special groups individually and collectively hinder participation in procurement opportunities.